2018
DOI: 10.3390/app8101958
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Plenoptic Imaging: An Overview

Abstract: Plenoptic imaging (PI) enables refocusing, depth-of-field (DOF) extension and 3D visualization, thanks to its ability to reconstruct the path of light rays from the lens to the image. However, in state-of-the-art plenoptic devices, these advantages come at the expenses of the image resolution, which is always well above the diffraction limit defined by the lens numerical aperture (NA). To overcome this limitation, we have proposed exploiting the spatio-temporal correlations of light, and to modify the ghost im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Several technologies have been developed in the field of quantum imaging, which go beyond the capabilities of standard imaging and interferometry systems [22][23][24][25][26][27][28][29][30]. * francesco.pepe@ba.infn.it Recently, a technique named Correlation Plenoptic Imaging (CPI) [31] has been shown to overcome the typical tradeoff between spatial and directional resolution of plenoptic imaging, by exploiting intensity correlations of either chaotic light [32][33][34][35] or entangled photon pairs [36]. The key idea of CPI is to encode information of the image and the direction of light in two distinct sensors: the desired information emerges by evaluating intensity correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies have been developed in the field of quantum imaging, which go beyond the capabilities of standard imaging and interferometry systems [22][23][24][25][26][27][28][29][30]. * francesco.pepe@ba.infn.it Recently, a technique named Correlation Plenoptic Imaging (CPI) [31] has been shown to overcome the typical tradeoff between spatial and directional resolution of plenoptic imaging, by exploiting intensity correlations of either chaotic light [32][33][34][35] or entangled photon pairs [36]. The key idea of CPI is to encode information of the image and the direction of light in two distinct sensors: the desired information emerges by evaluating intensity correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Further to the potential applications of quantum imaging schemes, it has been demonstrated that imaging schemes at conventional wavelengths can be improved by using quantum sources, either by enhancing the resolution or decreasing the noise of images [141,52]. Future developments in quantum imaging could come through new approaches such as quantum image processing [191] or through exploiting quantum correlations via different methods such as correlation plenoptic imaging [192]. Moreover, early demonstrations of principle of quantum imaging techniques are now more and more transforming into real world practical implementations from which new imaging technologies may emerge.…”
Section: Discussionmentioning
confidence: 99%
“…It allows to refocus an out of-focus image in post processing without using several detectors, multiple shots or time consuming scanning techniques. Lately a new technique, namely Correlation Plenoptic Imaging (CPI) [10], [11] has been proposed, combining GI and PI. By replacing the bucket detector in Ghost Imaging by a second detector array, directional and spatial information can be acquired simultaneously, similar to PI.…”
Section: Introductionmentioning
confidence: 99%